Innovative Methods in Education Supporting Formative Assessment of Students within the Subject Technology in Elementary School - Ďuriš, Milan (Journal of Education, Technology and Computer Science, ISSN 2719-6550, e-ISSN 2719-7417, 2019)
This article pays attention to formative assessment of students within the subject Technology in elementary school, where the emphasis is put on a feedback and a self-assessment of students. Innovative methods of teaching supporting formative assessment of students within the subject Technology are drafted from the didactic point of view in a university textbook, which constitutes one of the output solutions for given topic in the KEGA project. As a demonstration we would like to point out basic information regarding the teaching methodology for selected content of learning topics as well as example of learning task and its solution.